Development of pupils’ cognitive abilities - Sičiūnienė, Viktorija (Lietuvos matematikos rinkinys, 2018)
The article analyzes the situation of the development of cognitive abilities in Lithuania. It also introduces Revised Bloom Taxonomy and its application experiences in developed world countries. The emphasis is placed on the importance of applying Bloom-taxonomy to all levels of the education system in order to achieve higher student achievement.